2017
DOI: 10.1097/md.0000000000006770
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of serum alanine aminotransferase as biomarker for nonalcoholic fatty liver disease and insulin resistance in healthy subjects, using 3T MR spectroscopy

Abstract: Recognition of the close relationship of nonalcoholic fatty liver disease (NAFLD) with diabetes mellitus 2, obesity, metabolic syndrome, and cardiovascular disease has stimulated growing interest in NAFLD as a public health problem. Serum alanine aminotransferase (ALT) has been proposed as a marker of NAFLD, but levels are within the range currently considered “normal” in a large proportion of NAFLD subjects.The aim of the study was to determine the diagnostic accuracy of serum ALT for identifying individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 51 publications
(68 reference statements)
5
38
0
2
Order By: Relevance
“…NAFLD is usually caused by the abnormal metabolism in patients and tightly associated with dyslipidemia, diabetes mellitus and obesity [5]. Abundant studies and clinical practices have proven that the liver enzyme levels such as ALT and so on were increased usually in the NAFLD patients, and these liver enzymes could be used as the diagnostic markers for the NAFLD at some extent [29][30][31]. However, not all the studies supported the above conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD is usually caused by the abnormal metabolism in patients and tightly associated with dyslipidemia, diabetes mellitus and obesity [5]. Abundant studies and clinical practices have proven that the liver enzyme levels such as ALT and so on were increased usually in the NAFLD patients, and these liver enzymes could be used as the diagnostic markers for the NAFLD at some extent [29][30][31]. However, not all the studies supported the above conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Martin-Rodriguez et al (2017) showed a correlation of ALT with liver fat content and increased insulin resistance, suggesting that ALT, even when within the normal range, may be useful for NAFLD categorization when evaluating NAFLD's systemic relationships. This study shows that optimal serum ALT cut-off to predict NAFLD is 23 IU/L [47], although there is no general consensus on the upper reference limit of ALT (40 IU/l is the most common in medical practice). A study on obese patients showed that elevated ALT and GGT levels correlated significantly with the incidence of steatohepatitis and fibrosis [48].…”
Section: Discussionmentioning
confidence: 79%
“…Besides, former researches have con rmed that hepatic diseases like non-alcoholic fatty liver disease (NAFLD) were related to glucose metabolism and the prevalence of diabetes (21,22). And the elevation of liver enzymes such as ALT, AST and gammaglutamyl transpeptidase (GGT) or the ALT/AST ratio are treated as surrogate markers of NAFLD in common (23)(24)(25). Monami, M., et al have a rmed a undeniable relation between elevated liver enzyme levels and type 2 diabetes (T2DM) (26).…”
Section: Discussionmentioning
confidence: 99%